A pillar[5]arene-containing cross-linked polymer: synthesis, characterization and adsorption of dihaloalkanes and n-alkylene dinitriles. Issue 92 (20th September 2016) - Ye, Fengqing; Wei, Ruijin; Wang, Lingyun; Meier, Herbert; Cao, Derong
Abstract : A pillar[5]arene-containing cross-linked polymer was synthesized and utilized to adsorb dihaloalkanes and n -alkylene dinitriles. Abstract : A pillar[5]arene-containing cross-linked polymer was synthesized via Williamson reaction involving monohydroxy pillar[5]arene with chloromethylated polystyrene. Its adsorption behavior towards guests was investigated. It was found that the pillar[5]arene-containing polymer exhibited good adsorption capacities towards dihaloalkanes and dinitriles by host-guest complexation.